The Effect of Administrative Leadership on the Performance of Patient Experience: Empirical Study on the Administrative Employees In Jeddeh Health Affairs Directorate - Al-Ghamdi, Hossam; Taibah, Hassan (The Arab Journal of Administration, 2023)
The purpose of the study is to investigate the effect of administrative leadership on the performance of patient experience. The sample of the study consisted of all the population as it is a small one containing (110) administrators at Jeddeh Health Affairs Directorate selected through organized sampling in 1444H. After distributing the survey list via Google Drive, the correlation coefficient reached (0.687), which is a positive and statistically significant value according to the statistical significance value (0.000), which is less than the significance level (0.05), which indicates a significant positive relationship between the two variables. Thus, it is possible to reach the acceptance of the first hypothesis of the study, which states that: There is a statistically significant positive relationship between the provision of an independent environment for administrative staff and the performance of patient experience management for administrative staff at the Directorate of Health Affairs in Jeddah Governorate. The correlation coefficient was (0.779), which is a positive and statistically significant value according to the statistical significance value (0.000), which is less than the significance level (0.05), which indicates a significant positive relationship between the two variables. Thus, it can be reached to accept the second hypothesis of the study, which states that: There is a statistically significant positive relationship between the provision of material capabilities and aids for the administrative staff and the performance of patient experience management for the administrative staff at the Directorate of Health Affairs in Jeddah Governorate.